ВЛИЯНИЕ КОММУТАЦИОННОГО СОПРОТИВЛЕНИЯ ВЫПРЯМИТЕЛЯ НА УСТОЙЧИВОСТЬ ГОРЕНИЯ ЭЛЕКТРИЧЕСКОЙ ДУГИ ТЕХНОЛОГИЧЕСКОГО МИКРОПЛАЗМОТРОНА - Спирин, В.М. (Інститут електродинаміки НАН України, Київ, 2013)
Resistance switching three-phase bridge rectifier with RL load supplied from the power source is calculated. Based on the equivalent circuit of the rectifier for small deviations of the arc current condition stable combustion arc circuit current sourcе–three-phase bridge rectifier–inductance–operator arc resistance is defined. This condition is the same form as the criterion of Kaufman, but the function of the ballast resistance in this case is switching resistance. References 11, figures 7.